Morphological and molecular characterization of a fungus, Hirsutella sp., isolated from planthoppers and psocids in Argentina - Toledo, Andrea Vanesa (2013)
A mycosed planthopper, Oliarus dimidiatus Berg (Hemiptera: Cixiidae), and two psocids, Heterocaecilius sp. (Psocodea: Pseudocaeciliidae) and Ectopsocus sp. (Ectopsocidae), were collected from Los Hornos and La Plata, Buenos Aires, Argentina between February and September 2007. Observations of mycelia growing on the host revealed that the putative fungal parasite had synnemata supporting monophialidic conidiogenous cells. Likewise, in vitro fungal cultures presented characteristics typical of the fungus Hirsutella citriformis Speare (Ascomycota: Hypocreales: Clavicipitaceae). The identity of the isolated fungi characterized based on morphological aspects was complemented by means of the internal transcribed spacer sequences. The sequences of both isolates were highly homologous to those of Cordyceps sp. (Fries) Link and Ophiocordyceps sinensis (Berkely) G.H. Sung, J.M. Sung, Hywel-Jones, and Spatafora (Ophiocordycipitaceae). We additionally confirmed that both isolates had the ability to infect and kill adults of Delphacodes kuscheli Fennah (Hemiptera: Delphacidae) after 10 days. Therefore, based on the morphology of the isolated fungi, their ribosomal internal transcribed spacer sequence, and their ability to parasite insects, we conclude that the fungi isolated belong to the genus Hirsutella and might have biotechnological potential.